The Limits of Sectoral and Regional Efforts to Designate High Seas Marine Protected Areas. (9th July 2018) - Freestone, David
Abstract : This essay addresses the question of how the international community could designate high seas marine protected areas (MPAs) that would be binding on all states. This is a key issue for the forthcoming UN negotiations of an International Legally Binding Instrument (ILBI) on conservation and sustainable use of biodiversity in areas beyond national jurisdiction. However, this is a longstanding question, the importance of which transcends the ILBI negotiations. Some have argued for the establishment of a centralized Ocean Governance Authority, whose decisions would be universally binding; others have argued that existing regional and sectoral bodies can be relied on to protect biodiversity in areas beyond national jurisdiction. The experience of the Sargasso Sea project is that some sort of centralized or coordinating regime is needed to make MPAs effective across regional and sectoral bodies.